1-(3-Chlorophenyl)-4-(3-phenylseleno propyl) piperazine (L); synthesis, spectroscopic characterization, DFT studies, antimicrobial evaluation and its reactivity toward group 12 metal chlorides. Issue 16 (17th September 2018) - Bhat, Muzzaffar A.; Lone, Shabir H.; Srivastava, Sanjay K.
Abstract: C6 H5 Se − Na + (generated in situ by NaBH4 reduction of (C6 H5 Se)2 ) on reaction with ClC3 H6 C4 H8 N2 ClC6 H5 under N2 atmosphere results in C6 H5 SeC3 H6 C4 H8 N2 ClC6 H5 (L) as a cream-colored solid. Its 1:1 metal complexes having the general formula [MLX2 ], where M = Zn, Cd, Hg, and X = Cl, have been prepared. Ligand L and its complexes1–3 are characterized on the basis of physico-chemical and spectral (FT-IR, ESI Mass, 1 H, 13 C, DEPT 135° 13 C { 1 H}, and 77 Se{ 1 H} NMR) studies. IR spectroscopy revealed that L is coordinated solely through selenium and nitrogen to zinc, cadmium, and mercury ions forming a six-membered chelate ring around M(II) ions. Elemental analysis measurements along with 1 H, 13 C, DEPT 135° 13 C { 1 H}, and ESI-mass data also confirm the bidentate coordination mode of the ligand. Moreover, the coordination from selenium atom is also supported by the downfield shift of signal in 77 Se{ 1 H} NMR spectroscopy. Using DFT-based optimization of structures, the HOMO-LUMO energy gaps and molecular electrostatic potential surface of ligand L and complexes1–3 were theoretically calculated at the B3LYP/LANL2DZ level of theory. Ligand L and complexes1–3 display significant antibacterial and antifungal activity. Graphical Abstract: